Recruitment of Indigenous Australians with linguistic and numeric disadvantages - Pearson, Cecil (Singapore Human Resources Institute, 2012)
Recruitment challenges for mining corporations operating in Australia have intensified with the increasing global demand for mineral resources and the 1993 Native Title legislation compelling negotiated land use agreements. A finite labour pool, further compressed by an ageing and retiring workforce, competition for labour, a poor industry image as well as a requirement for applicants to possess particular educational and vocational competencies has not been offset by greater Indigenous participation, despite training provisions being a feature of land use agreements. This paper presents an analysis of a novel recruitment technique that is devoid of the need for English literacy and numeracy skills, for Indigenous people with expectations to be employed in the extensive mining operations at Nhulunbuy on the Gove Peninsula of the Northern Territory (NT) of Australia. Predicating the scheme design was a comprehensive literature reporting that the English literacy and numeracy skills likely to be held by Australian Indigenous people would preclude them from usefully participating in standard Western recruitment procedures. Analyses reveal that the scheme is a robust predictor of sustainable employment. This leads to a line of reasoning that discriminatory recruitment practices can be substituted with alternative methods to identify human work related potential and, subsequently, address economic challenges and social dislocation of marginalised Indigenous groups.